ANALYSIS OF THE INFLUENCE OF TEACHING METHODS ON STUDENTS' ACADEMIC EMOTIONS DURING SYNCHRONOUS INTERACTION USING AI - Hlazunova, Олена; Savytska, Інна; Kravchenko, Володимир; Korolchuk, Валентина; Voloshyna, Тетяна; Саяпіна, Таїсія (Journal of Information Technologies in Education (ITE), 2025)
In modern education, an important factor in the quality of specialist training at different levels of training and educational programs is the determination of students' academic emotions. Taking this factor into account by teachers of educational institutions can significantly affect the level of organization of the educational process, student's academic performance, their ability to learn different types of educational content depending on the method of teaching, as well as affect motivation and satisfaction by controlling their level of attention and engagement during synchronous interaction. The paper analyses students' academic emotions during lectures using different teaching methods and investigates their impact on attention and engagement. The pedagogical experiment was conducted among the 2nd year Bachelor's degree students majoring in 121 ‘Software Engineering’ at the Faculty of Information Technology of the National University of Life and Environmental Sciences of Ukraine (NULES). The study used three teaching methods during online lectures in synchronous mode, namely: visual (demonstration of presentation slides); brainstorming method (discussion of key issues of the lecture); case method (demonstration of a practice-oriented task), as well as a AI tool (MorphCast Emotion AI) for recognizing students' academic emotions in real-time. MorphCast Emotion AI allows the teacher to track the level of student engagement during a synchronous lecture, offering recommendations based on the data obtained, when to take breaks, how to adapt and adjust teaching methods, forms of educational content delivery, or adapt the sequence of topics within the discipline. After the class, detailed statistics on the level of engagement and attention help to plan further synchronous courses, ensuring that each online lecture is as effective and efficient as possible for students in today's environment.